Evaluasi Standar Pelayanan Bus Pariwisata Pada Kegiatan Project Based Learning (PBL) Mahasiswa - Laily; Neysa Hidayat; Nura Nazma Lu’lu’a; Zahwa Febriyanti; Davina Eka Putri; Novia Eka Safitri; Yuriko Inkanori Jatmiko; Muhamad Ari Perdana (CV. ITTC INDONESIA, 2026)
This study aims to evaluate the levels of security, safety, and comfort of the tour buses used by students in the Tourism Department at Banyuwangi State Polytechnic during Project-Based Learning (PBL) activities in Bali, based on the Minimum Service Standards (SPM) for Tourist Transportation. The research method used was quantitative descriptive, with data collection techniques including questionnaires and direct observation. The study respondents consisted of 44 students who used Bus 1 and 38 students who used Bus 3. The data were analyzed using scores, percentages, and a continuum scale. The results showed that all indicators fell into the “high” category. For Bus 1, the security aspect scored 80%, safety 79%, and comfort 87%. Meanwhile, on Bus 3, the security aspect scored 79%, safety 76%, and comfort 83%. The comfort aspect was the indicator with the highest score on both buses. However, some facilities were still not optimally available, such as CCTV, safety briefings, passenger tickets, luggage tags, and emergency response manuals. Overall, both buses have met passengers’ expectations in providing safe, secure, and comfortable service.